The Central Role of Redox-Regulated Switch Proteins in Bacteria - Fassler, Rosi; Zuily, Lisa; Lahrach, Nora; Ilbert, Marianne; Reichmann, Dana (Frontiers in Molecular Biosciences, 2021)
Bacteria possess the ability to adapt to changing environments. To enable this, cells use reversible post-translational modifications on key proteins to modulate their behavior, metabolism, defense mechanisms and adaptation of bacteria to stress. In this review, we focus on bacterial protein switches that are activated during exposure to oxidative stress. Such protein switches are triggered by either exogenous reactive oxygen species (ROS) or endogenous ROS generated as by-products of the aerobic lifestyle. Both thiol switches and metal centers have been shown to be the primary targets of ROS. Cells take advantage of such reactivity to use these reactive sites as redox sensors to detect and combat oxidative stress conditions. This in turn may induce expression of genes involved in antioxidant strategies and thus protect the proteome against stress conditions. We further describe the well-characterized mechanism of selected proteins that are regulated by redox switches. We highlight the diversity of mechanisms and functions (as well as common features) across different switches, while also presenting integrative methodologies used in discovering new members of this family. Finally, we point to future challenges in this field, both in uncovering new types of switches, as well as defining novel additional functions.